Online Engineering Education and Regional Growth: Innovation, Digitalization, and Policy - Cai, Wei; Sufian, Jusoh; Radin A Rahman, Siti Aishah; Wang, Si Ya (International Journal of Online and Biomedical Engineering (iJOE), 2025)
Building upon traditional research on engineering education, innovation, and economic growth, this study introduces additional control variables such as air quality and talent concentration and extends the analytical scope to include underdeveloped regions in western China, thus advancing beyond conventional research paradigms. The research investigates the impact of high-quality engineering education on regional economic sustainability across nine diverse Chinese regions from 2014 to 2024. Grounded in regional innovation systems theory, the study examines both the direct effects of educational investment on economic outcomes and indirect effects mediated through innovation, digital transformation, and industrial upgrading. Findings indicate that financial investment in engineering education significantly promotes regional economic growth, although effects differ notably across regions. Developed areas in China experience economic growth primarily driven by innovation, whereas regions such as Henan and Heilongjiang rely more on industrial modernization. Additional control variables, including R&D personnel density and air quality, further influence these relationships. The study emphasized the importance of zoning to promote optimization of school investment.